PUBLIC AND PRIVATE AGRICULTURAL EXTENSION SERVICES AS SOURCES OF INFORMATION FOR CAPACITY BUILDING OF SMALLHOLDER FARMERS IN - U. Talib; I. Ashraf; R. Agunga; K. M. Chaudhary (Journal of Animal and Plant Sciences, 2018)
Agricultural extension is the main instrument for capacity building of smallholder farmers in Pakistan. Capacity building, in this study, is defined as the ability to gain knowledge and skills of recommended technologies that improve farmersperformances. Since the early 1990s, the government of the Islamic Republic of Pakistan endorsed private extension in an effort to enrich the effectiveness of public extension through competition. This research, conducted in 2016, sought to determine whether private extension providers are more effective than public extension as information sources for smallholder farmers. The specific objectives were to examine the effectiveness of Information and Communication Technologies (ICTs) use by public and private agricultural extension providers and to analyze statistically, the performances of public and private extension systems. A sample of 342 farmers drawn from a list of 2,365 rice growers registered with public and private offices in Gujranwala, the largest rice-producing district in Pakistan, were interviewed. The study found that extension agents in the private sector were less effective than the public sector, in communicating development messages to resource-poor farmers. However, the private sector was more effective in inputs distribution than the public sector. The authors suggest ways public and private extension workers can be more effective in strengthening the capacities of smallholder farmers. information and communication technologies, and agricultural extension. the nationrsice belt, accounting for 58% of total national
Keywords: capacity building; smallholder farmers; public and private extension services; agricultural extension